2022
DOI: 10.21931/rb/2022.07.04.15
|View full text |Cite
|
Sign up to set email alerts
|

Wheat seed deterioration stimulated by plant extracts

Abstract: During 2019-2020, the experiment was conducted in the laboratory of the Department of Field Crop Sciences, Faculty of Agricultural Engineering Sciences - Baghdad University, to investigate the impact of soaking wheat seeds produced during the 2016 agricultural season with three plant extracts (licorice root extract 2%, 4% and 6%, Acadian and Humic(500, 1000, & 1500 mg L-1). Aside from the two control treatments (soaking in distilled water with dried seeds). The results show that the soaking treatment with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…To monitor whether L. album extract alters the mycotoxin biosynthesis in wheat seedlings, an analysis was conducted, revealing that the content of mycotoxins, including DON, 3-and 15-AcDON, ZEN, and ZEN-14S, commonly associated with F. culmorum contamination (Bryła et al, 2018;Uwineza et al, 2022), were reduced both in roots and leaves of seedlings treated with L. album extract. Abbas and Yli-mattila (2022) showed that the methanolic extract of the medicinal plant Zanthoxylum bungeanum successfully decreased F. graminearum growth and abrogated DON production in wheat heads (Abbas and Yli-mattila, 2022). Similarly, Shcherbakova et al (2018) found no increase in DON, AcDON, and ZEN content when F. culmorum and F. graminearum developed on extract-treated wheat seeds and seedlings (Shcherbakova et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To monitor whether L. album extract alters the mycotoxin biosynthesis in wheat seedlings, an analysis was conducted, revealing that the content of mycotoxins, including DON, 3-and 15-AcDON, ZEN, and ZEN-14S, commonly associated with F. culmorum contamination (Bryła et al, 2018;Uwineza et al, 2022), were reduced both in roots and leaves of seedlings treated with L. album extract. Abbas and Yli-mattila (2022) showed that the methanolic extract of the medicinal plant Zanthoxylum bungeanum successfully decreased F. graminearum growth and abrogated DON production in wheat heads (Abbas and Yli-mattila, 2022). Similarly, Shcherbakova et al (2018) found no increase in DON, AcDON, and ZEN content when F. culmorum and F. graminearum developed on extract-treated wheat seeds and seedlings (Shcherbakova et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…The effect of Lamium album flower extract on the germination of wheat kernels was determined according to Al-Khafajy et al (2022) with some modifications. Ten mL solution of L. album flower extract was prepared at 5% and 10% concentrations, then added to sterilized glass plates with tissue paper containing sterile 10 grains/plate; the control samples were prepared with 10 mL of distilled water, and aseptically prepared plates (four plates for each treatment) were incubated under controlled whirlpool chamber at 28 • C for 7 days.…”
Section: Standards Chemicals and Reagentsmentioning
confidence: 99%
“…The seaweed extract contained alginates, polysaccharides laminarin, carrageenans, and their degradation products, in addition to containing compounds related to stimulating plant growth, such as macro and microelements, sterols, betaines, and hormones such as cytokinins, auxins, , and gibberellins [11,12]. Seaweed extract has many benefits because it improves the vitality and germination of seeds, and this was supported by [13], by increasing the plant absorption of nutrients. The plant gains resistance to frost and fungal diseases in addition to the extract; Seaweed effectively increases the shelf-life and fruit ripening of the horticultural product and improves its quality and soil conditions.…”
Section: Introductionmentioning
confidence: 99%